(untitled) (Indian Journal of Arid Horticulture, 2017)
The major insect pollinators included Hymenoptera, Diptera, a few Lepidoptera, Hemiptera and Coleoptera. Among these, the mean of total hymenopterans visiting the umbels of coriander during the entire flowering period happened to be 18.89/plant/minute-observation/day; within hymenopterans, A. florea and A. dorsata were the most dominant forming 91.54 per cent. The foraging activity of A. florea was more pronounced during 12-2 p.m. (1.312 bees/ day/ plant/ minute observation), whereas the foraging activity of A. dorsata was maximum during 8-10 a.m. (0.032 bees/ day/ plant/ minute observation). A. florea formed 38.86 (8-10 a.m.), 86.36 (12-2 p.m.) and 27.43 (4-6 p.m.) per cent of the total insect pollinators, the corresponding figures for A. dorsata were 9.35 (8-10 a.m.), 1.18 (12-2 p.m.), and 2.26 (4-6 p.m.) per cent. The total dipterans that visited the umbels of coriander during the entire flowering period happened to be 0.36- flies/plant/minute/day. The family Muscidae was most dominant with 0.26-flies/plant/minute/day. The foraging activity of muscid flies was the maximum during 4-6 p.m. (0.094-flies/ plant/minute/day) forming 26.70 per cent. Otherwise too, Dipterans happened to be the maximum during 4-6 p.m. (0.061-flies/plant/minute/day) followed by that at 8-10 a.m. (0.035- flies/plant/minutes/day). The other insect pollinators included insects of Lepidoptera, Hemiptera and Coleoptera and their numerical abundance formed 0.107-insects/plant/minute/day. Of these, hemipteran visitors dominated with 0.091- bugs/plant/minute/day. The foraging activity of Hemiptera was the maximum during 4-6 p.m. (10.01 % ) and minimum during 12-2 p.m. (1.98% ). On the basis of the seven class-interval categories that could be identified, most insect pollinators happened to fall under the category of 1-5 insects per unit of observation.